Power Quality Improvement in Solar Integrated Power Systems Using Fuzzy-Based MMC UPQC - Garikapati, Rajesh; Kumar, S. Ramesh; Karthik, N. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Fuzzy-based MMC-UPQC in solar-integrated power systems to enhance power quality is proposed in this work. Due to power electronic switches in solar integration systems and in the nonlinear loads, harmonics and voltage sag and swells will impact other equipment and other consumers in the power systems. The proposed work aims to suggest the adoption of a Modular Multilevel Converter (MMC) based Unified Power Quality Conditioner (UPQC) to improve the power quality of medium and high-voltage solar-connected power systems. The proposed MMC-UPQC is highly unified and has reduced DC-link voltage, effectively isolated harmonics, and improves voltage regulation in the main system. To explain this work establishes the switching strategy of the MMC by examining how it suppresses harmonics and regulates the voltage. Based on this analysis, the paper designs a compound control strategy that combines a series and shunts hybrid active power filter and a synchronous method using SGDFT (Sliding-Mode Generalized Discrete Fourier Transform) filtered PLL (Phase Locked Loop). A fuzzy controller is adopted as DC voltage regulator due to its capability to manage uncertainties and nonlinearities in the system. The system utilizes a collection of fuzzy rules that enable the mapping of input signals to the output signal, thus rendering it appropriate for deployment in situations where the system dynamics are intricate. Finally, the paper validates the performance of the MMC-UPQC in a supply system using MATLAB/Simulink simulations. By analysing simulation results, the effectiveness of the MMC-UPQC in regulating control grid energy, suppressing load harmonic current, and compensating for immediate control is demonstrated.